Abstraction of the Document of General Ideas; An Argument for the Immateriality of the Soul - Ahmad Reza Kafrashi; Hassan Yousofian (آموزه‌‌های فلسفه اسلامي, 2021)
Anthropology is one of the most important topics in influencing our understanding, explanation and interpretation of religious teachings. The discussion of human essences is one of its most fundamental parts. Islamic philosophers and some theologians believe in the immateriality of the soul. Some theologians deny the immateriality of the soul and consider it material. From the beginning of the formation of theological schools until now, sometimes materialism (corporealism) and sometimes incorporealism (incorporeality) have been the dominant theory. In the last century, although the view of abstractionism is the dominant theory, theologians of the school of separation (disassembly) have defended the materiality of the soul. Incorporealist present a number of arguments to prove the abstraction of the soul. One of the most important of them is the proof that proves the abstraction of the soul through the perception of general ideas by the soul. In this argument, it concludes the incorporeality of the soul as the place of these forms, sometimes through the accidents of being material perceived intelligibles and sometimes through the absence of material effects that perceived intellects. This research has investigated this reason by descriptive-analytical method. The correctness (verification) and extent of its indication were examined after explaining it, and it became clear that there are several forms that have been included in both expressions of this rational proof; cannot damage the validity of this argument.